Ecologic planning and application of broadband access network based on geographic grid - Qi ZHANG (Dianxin kexue)
With the development of broadband services,fixed broadband access network is at the top speed in construction.Multi-carriers pay more attention on both network scale and ability to keep the necessary advantages in access availability and effectiveness.On the other hand,the network construction is also depended on both the co-operation with service development and the match with fundamental resources.The balance of the above factors is the key role in actual network planning and construction.Considering the present planning method of broadband access network,the bottleneck was analyzed and concluded.Based on multi-dimension geographic grid,the ‘cubic model’,containing services,network ability and fundamental resources,were also developed and introduced.Finally,supported by the big data of network statistic,the model was applied and also verified in actual planning environment on the according self-researched planning platform.